Desain Karakter pada Buku Ilustrasi Mengenai Suicidal Thoughts untuk Generasi Z - Aimmatus Solikah; Restu Ismoyo Aji; Pungky Febi Arifianto (IAI Nasional Laa Roiba Bogor, 2026)
The issue of suicidal thoughts among Generation Z has become a serious concern, marked by the high prevalence of depression and suicidal ideation within this age group. This article discusses the strategy for designing characters for an illustrated book addressing suicidal thoughts among individuals aged 17 to 21. Through a comprehensive, mixed-methods methodology incorporating interviews with mental health professionals and illustrators, surveys of target audience respondents, and comparative visual analysis, this research creates characters that serve as both educational tools and emotional anchors. The final outcome is the design of two characters that represent physical characteristics, visual styles, and emotional markers relevant to the Gen Z experience. The design approach thoughtfully integrates aspects of personal identity, social pressures, and psychological expression. This character design strategy not only fosters reader empathy but also establishes an emotional connection, making complex mental health topics more accessible and understandable.